2005
DOI: 10.1590/s0100-204x2005000900003
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição ambiental de poluentes orgânicos encontrados em lodos de esgoto

Abstract: Resumo -O objetivo deste trabalho foi apresentar uma modelagem da distribuição ambiental de vinte e nove poluentes orgânicos encontrados em amostras de lodos de esgoto das estações de tratamento de esgoto de Barueri e Suzano, SP. Lodos de esgoto são misturas de produtos orgânicos e inorgânicos gerados nos processos primários e secundários de tratamento que, mediante adequado controle de qualidade, podem ser reutilizados como fertilizantes agrícolas. O modelo de fugacidade nível I foi aplicado a um sistema comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
(17 reference statements)
0
3
0
5
Order By: Relevance
“…The phenanthrene (light PAH) characteristics such as low lipid affinity, relatively high water solubility and high vapor pressure favor its preferential uptake by plants, in this case maize plants, and its transport to grains. 19,25 In this research, the SS analysis revealed 67% of PAHs with two, three or four aromatic rings (light PAHs) and 33% with five or six aromatic rings (heavy PAHs). Sewage sludge PAH and other compound contents may be seasonal dependent, and retention and bioavailability in soil samples depend on sorption, water solubility, and charged functional groups in the molecules.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…The phenanthrene (light PAH) characteristics such as low lipid affinity, relatively high water solubility and high vapor pressure favor its preferential uptake by plants, in this case maize plants, and its transport to grains. 19,25 In this research, the SS analysis revealed 67% of PAHs with two, three or four aromatic rings (light PAHs) and 33% with five or six aromatic rings (heavy PAHs). Sewage sludge PAH and other compound contents may be seasonal dependent, and retention and bioavailability in soil samples depend on sorption, water solubility, and charged functional groups in the molecules.…”
mentioning
confidence: 62%
“…Among the pollutants, Dreher 23 studied the classes of PAHs, polychlorinated biphenyls, chloride pesticides, dioxins and furans, octil-nonylphenols, polycyclic mixtures, phthalates, polybrominated diphenyl ethers, organotins, linear alkylbenzene sulfonates, bisphenols, pharmaceutical products and heavy metals. Krogmann 24 and Paraíba and Saito 25 pointed out the need of continuous organic pollutant monitoring in sewage sludges from different origins.…”
Section: Introductionmentioning
confidence: 99%
“…Conclui-se também, a partir dos valores de pressão de vapor e da constante de Henry (K H = 1,2 x 10 -3 L atm/mol), que a perda por volatilização é insignificante. 7,9 Estudos mostram que o tempo de meia-vida por biodegradação no solo é de 120 a 309 dias. Toxicologicamente, o BaP é considerado como carcinogênico, mostra efeitos embriotóxicos e teratogênicos.…”
Section: Propriedades Do Benzo(a)pirenounclassified
“…Rodríguez-Morgado et al (2015) also highlighted that the use of different types of SS in the soil can generate distinct enzymatic activities due to the variation in the microbiological community present in each SS. Due to the SS environmental risks, its growing world production and its rich composition of organic matter and nutrients (e.g., nitrogen, phosphorus, potassium, calcium, copper, cadmium, zinc, and manganese), some researchers have suggested the use of SS as an agricultural Nevertheless, SS can also contain harmful substances for living organisms and the environment, such as copper, nickel, lead, cadmium, and mercury, in addition to organic compounds, such as phenols, benzenes, anthracenes, linear sulfonated alkylbenzenes, and pathogenic microorganisms (Almeida et al, 1998;Holmstrup et al, 2001;Lopes et al, 2005;Lourenço, 1997;Paraiba and Saito, 2005).…”
Section: Introductionmentioning
confidence: 99%